Application of bile acids in drug formulation and delivery - Stojancevic, M.; Pavlovic, N.; Golocorbin-Kon, S.; Mikov, Momir (Taylor & Francis, 2014)
Bile acids are naturally produced in humans and are known to provide human health benefits through their endocrinological, microfloral, metabolic and other åffects that are still to be elucidated. In recent years, there has been a growing interest in using bile acids as absorption enhancers for drug delivery. Bile acids are amphiphilic molecules with a unique ability to facilitate and promote drug permeation through biological membranes. The role of bile acids in promoting drug permeation has been experimentally illustrated in various pharmaceutical formulations including oral, nasal, ocular, buccal, pulmonary and rectal delivery as well as through the blood–brain barrier. Recently, bile acids have drawn attention in the field of drug delivery due to their ability to act as a drug carrier system in the form of mixed micelles, bilosomes and chemical conjugates with drug molecules. Bile acids have demonstrated a unique ability to enhance the epithelial transport of hydrophilic drugs through the paracellular route and that of hydrophobic compounds through both paracellular and transcellular routes. The aim of this review is to discuss various chemical and pharmaceutical aspects of BAs and their potential applications in drug formulation and delivery.